1992
DOI: 10.3168/jds.s0022-0302(92)78079-5
|View full text |Cite
|
Sign up to set email alerts
|

Milk Composition of Majaheim Camels

Abstract: To determine composition, milk samples were obtained at random from camels at two camel rearing areas near Riyadh, Saudi Arabia. Proximate analyses indicated 3.15% fat, 2.81% protein, 4.16% lactose, 10.95% total solids, .15% acidity, .83% ash, and 88.33% water. Mineral composition was (milligrams per gram) 30.03, Ca; 72.48, K; 43.10, Na; .28, Fe; .18, Pb; and 4.50, Mg. Results should contribute to the overall knowledge of camels as a food source, but much still needs to be learned if efficient improvement prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
26
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 4 publications
15
26
4
Order By: Relevance
“…Therefore, camel milk can be considered as a good source of these minerals for human. These findings were in agreement with the results reported by [9,18,26,34,35,37,43]. However, Farida and Srikumar [44] reported that the concentration of manganese and iron in camels' milk was higher (7-20-fold and 4-10-fold, respectively) than in human milk, cows 'milk and infant formula.…”
Section: Basic Composition Of Camel Milksupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, camel milk can be considered as a good source of these minerals for human. These findings were in agreement with the results reported by [9,18,26,34,35,37,43]. However, Farida and Srikumar [44] reported that the concentration of manganese and iron in camels' milk was higher (7-20-fold and 4-10-fold, respectively) than in human milk, cows 'milk and infant formula.…”
Section: Basic Composition Of Camel Milksupporting
confidence: 91%
“…These results are in consonance with the results of Wernery et al [35]. The fat content in the present study was found lower in comparison to that of fat content noted in camels by [5,18,23,26,28,29,31,32,36,37]. This low percentage is certainly due to an environmental difference reflecting the desert nature of our country.…”
Section: Basic Composition Of Camel Milksupporting
confidence: 91%
See 3 more Smart Citations